Performance of lightweight aggregates concrete with substitution of aluminum flakes as fine aggregates - Adnan, Suraya Hani; Kosenin, Nini Azrin Amiera (Penerbit Uthm, 2017)
Concrete is a high demanded construction material nowadays. The current modernization has improved the use of concrete in the construction industry. Thus, the production of lightweight concrete is introduced to replace the use of normal concrete in certain applications. With the current emphasis on upgrading structure, lightweight concrete provides more benefits since it reduces the dead weight of a concrete structure, which results a decrease in cross-section of structural members and steel reinforcement. The strength, durability and other characteristics of this concrete depend on the properties of the ingredients, its proportions of mix and method of compaction and other control during placing, compaction and curing. It is either a total combination of fine and coarse lightweight aggregates or a combination of coarse - fine lightweight aggregate with normal aggregates. Since aggregates, cement, water and air have different specific, weights, the overall density of a concrete mix will depend upon the relative amounts of these materials present [1]